The influence of self-efficacy and psychological well-being on the organizational commitment of 'Aisyiyah early childhood education teachers in the ex-Karesidenan Kedu - Mu'arifah, Alif; Bernadian, Hamas (Journal of Early Childhood Care and Education, 2024)
The role of PAUD teachers is increasingly complex along with the dynamics of education. Teacher commitment is a key factor in facing these challenges. This research aims to analyze the influence of self-efficacy and psychological well-being towards the commitment of 'Aisyiyah PAUD teacher organization in Kedu Residency area. Quantitative research method by design correlational study used in this study. The research sample consisted of 253 non-ASN formal PAUD teachers selected by purposive sampling. Multiple linear regression analysis shows that self-efficacy and psychological well-being simultaneously have a significant influence (F=18.675, p<0.01) on the organizational commitment of PAUD 'Aisyiyah teachers, contributing 34.6%. Partially, psychological well-being demonstrated a significant effect of 30.95%. These findings indicate the importance of development self-efficacy and improving the psychological well-being of PAUD teachers to strengthen their commitment to carrying out their duties.